Expressão de receptores de EGF, inibidores e reguladores do ciclo celular em lesões proliferativas da próstata canina - Faleiro, Mariana Batista Rodrigues (2014)
Somedysplastic lesionsof prostate, such as proliferativeinflammatoryatrophy (PIA) and prostatic intraepithelial neoplastic(PIN) are proliferative,consideredpremalignant andcan progress toprostatic carcinoma (PC). Others, such asbenign prostatichyperplasia(BPH) are proliferative, butare not related tomalignancy.The humanPC is the one ofcancers that more kill,and dog`sthe onlyanimal species thatpresentsadiseasewith similarcharacteristics, thishas been usedas a modelfor studyof prostatecancer. Thus, in order tobetter understandthe molecular mechanisms involvedin repairand cell cycleevolution ofproliferative lesionsincanine prostate, this study aimed to evaluatethe gene expression ofErbB1, ErbB2, CDKN1A, CDKN1BandTP53andimmunostaining ofEGFR(Her1), Her2(c-erbB-2), p21, p27and p53 inprostateswithPIAandPC. Also was evaluatedtheimmunostaining ofp21, p27, p53, c-myc andcyclinD1inprostateswith BPH, PIA, PINandPC. For this purpose,wereobtained from atissue microarray (TMA)block, 106samplesofcanineprostate tissue, which 15 normal, 16with BPH, 30 withPIA, 20 with PIN, and 25with CP. The RT-PCR andRT-qPCR techniques wereused to evaluategene expression, as well as immunohistochemistrywas used to determinetheimmunophenotypeofprostatic lesions. As forEGFRand Her2has beenobserved that thesereceptorsactin canine lesions withPIA and with PCan importantaction ofHer2, suggesting that theyare involvedin carcinogenesisandtumor development in canineprostate. Regarding to cellcycleinhibitor concludethat whenoverexpressedin canine prostateswithPIAandPC, p21andp27control cellproliferation, acting as a protective factorin the evolution of PIA to PC, and in the PC development, even in the presence of altereted p53. In assessing ofimmunostaining ofcell cycle regulators(p21, p27, p53, cyclinD1andc-myc) in canineprostateswithproliferative lesionswas observedthatcarcinomas probably have lowgrowth potentialwhenoverexpressed of p21andp27, reduced expression of cyclinD1and unalteredexpression ofc-myc, even in the presence ofmutant p53type.Further,considering thesimilarimmunophenotypein canine glands with PIA, PINandPC considered the regulatorsofcell cycle progression, it is reinforce the pre-malignant potential of PIA andPINin the canineprostate.